Green Tea Potentially Ameliorates Bisphenol A-Induced Oxidative Stress: An In Vitro and In Silico Study - Hiral Suthar; R. J. Verma; Saumya Patel; Y. T. Jasrai (Biochemistry Research International)
The present investigation was an attempt to elucidate oxidative stress induced by bisphenol A on erythrocytes and its amelioration by green tea extract. For this, venous blood samples from healthy human adults were collected in EDTA vials and used for preparation of erythrocytes suspension. When erythrocyte suspensions were treated with different concentrations of BPA/H2O2, a dose-dependent increase in hemolysis occurred. Similarly, when erythrocytes suspensions were treated with either different concentrations of H2O2 (0.05–0.25 mM) along with BPA (50 μg/mL) or 0.05 mM H2O2 along with different concentrations of BPA (50–250 μg/mL), dose-dependent significant increase in hemolysis occurred. The effect of BPA and H2O2 was found to be additive. For the confirmation, binding capacity of bisphenol A with erythrocyte proteins (hemoglobin, catalase, and glutathione peroxidase) was inspected using molecular docking tool, which showed presence of various hydrogen bonds of BPA with the proteins. The present data clearly indicates that BPA causes oxidative stress in a similar way as H2O2 . Concurrent addition of different concentrations (10–50 μg/mL) of green tea extract to reaction mixture containing high dose of bisphenol A (250 μg/mL) caused concentration-dependent amelioration in bisphenol A-induced hemolysis. The effect was significant (P<0.05). It is concluded that BPA-induced oxidative stress could be significantly mitigated by green tea extract.